Educational Considerations, vol. 10(3) Full Issue - Charles E. Litz; Gerald D. Bailey; Eddy J. Van Meter; Susan J. Scollay (Educational Considerations, 1983)
Educational Considerations, vol. 10(3) Fall 1983 - Full issue